KEABSAHAN AKTA HIBAH YANG DITANDATANGANI DALAM KEADAAN SAKIT FISIK - TIROMSI SITANGGANG (PREMISE LAW JURNAL, 2015)
The validity of the above grant signed by penghibah in sickness in the civil law can be justified by the law on the grounds that at the time of execution of the grant grantor can communicate well, have good hearing, able to recognize the penghadap, able to provide a signature, is able to understand the intent and purpose of making grants and conducted under the provisions of the legislation. The position of the other heirs of the grant is awarded when the grantor in a state hospital under civil law still serves as the heirs of the grantor along no circumstances cancel the inheritance. Implementation grants can still be made in accordance with procedures and applicable laws. Cancellation grant deed given when the grantor in a state hospital under civil law because of noncompliance with the terms of the grant Keywords: Grant Deed, Signed, Sick